Analisis Efektifitas Penerimaan Pajak Daerah Pada Kantor Badan Pendapatan Daerah di Kabupaten Gowa - Arwin arwin; Besse Faradiba; Wardianto Wardianto (Journal of Economics and Regional Science, 2021)
This study aims to determine the effectiveness of local tax revenues in Gowa Regency with a span of time for the last 6 years, namely 2013-2018. The analytical method used in this research is quantitative method and descriptive analysis, while the analytical tool used in this research is effectiveness analysis. Besides, qualitative analysis is also used in the form of direct interviews with local officials. The results of this study indicate that the regional tax revenues in Gowa Regency are broadly in the effective category. The factors that play a role in influencing the status of the effectiveness of regional tax revenues, namely the integrity of the taxpayer, the obligation to carry out tax payments in a timely manner, the local tax collection supervision system and the mechanism for collecting local taxes in Gowa Regency.